2021
DOI: 10.1002/ange.202109349
|View full text |Cite
|
Sign up to set email alerts
|

Selective Detection of Cu+ Ions in Live Cells via Fluorescence Lifetime Imaging Microscopy

Abstract: Copper is an essential trace element in living organisms with its levels and localisation being carefully managed by the cellular machinery. However, if misregulated, deficiency or excess of copper ions can lead to several diseases. Therefore, it is important to have reliable methods to detect, monitor and visualise this metal in cells. Herein we report a new optical probe based on BODIPY, which shows a switchon in its fluorescence intensity upon binding to copper(I), but not in the presence of high concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Priessner et al. designed a BODIPY‐based fluorescent probe FLCS1, and its structural formula is shown in Figure 9a [54] . When the NS 4 copper(I) acceptor in FLCS1 binds to copper(I), the fluorescence lifetime of the probe increases significantly (Figure 9b).…”
Section: Applications Of Lifetime‐based Responsive Probes In Biologic...mentioning
confidence: 99%
See 2 more Smart Citations
“…Priessner et al. designed a BODIPY‐based fluorescent probe FLCS1, and its structural formula is shown in Figure 9a [54] . When the NS 4 copper(I) acceptor in FLCS1 binds to copper(I), the fluorescence lifetime of the probe increases significantly (Figure 9b).…”
Section: Applications Of Lifetime‐based Responsive Probes In Biologic...mentioning
confidence: 99%
“…FLIM images of cells (c) before and (d) after incubated with Cu‐GTSM. Reproduced with permission [54] . Copyright 2021, Wiley‐VCH.…”
Section: Applications Of Lifetime‐based Responsive Probes In Biologic...mentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] This kind of chemodynamic therapy has been widely used in antitumor research. [10][11][12] In addition, the previous studies have demonstrated that copper can promote the growth of endothelial cells and angiogenesis. [13][14][15] Therefore, reducing the content of copper in cells via copper chelators can inhibit the growth of cells and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence lifetime imaging (FLIM) is a vital and versatile technique for assessing molecular microenvironments of fluorophores in living cells, such as pH, O 2 , viscosity, temperature, or ion concentrations [1,2]. FLIM can be a powerful "quantum ruler" to measure subnanometer protein conformational changes and interactions by quantifying the occurrence of Förster Resonance Energy Transfer (FRET) [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%